2019
DOI: 10.1101/697656
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neurotensin receptor 1 deletion suppresses methamphetamine self-administration and the associated reduction in dopamine cell firing

Abstract: We previously reported that pharmacological blockade of neurotensin receptors in the ventral tegmental area (VTA) decreases methamphetamine (METH) self-administration in mice. Here we explored the consequences of genetic deletion of neurotensin receptor 1 (NtsR1) in METH self-administration and VTA dopamine neuron firing activity. We implanted mice with an indwelling jugular catheter and trained them to nose-poke for intravenous infusions of METH. Mice with NtsR1 deletion (KO) acquired selfadministration simil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…This is consistent with previous reports of 2-to-3-fold higher NT levels in the SNc and dorsal striatum following methamphetamine self-administration (Frankel et al, 2011;Hanson et al, 2013). Furthermore, we have shown that blockade or ablation of NT receptors decreases methamphetamine selfadministration (Dominguez-Lopez et al, 2018;Dominguez-Lopez et al, 2019). Taken together, this suggests that methamphetamine use enhances NT-induced LTDDA, disinhibiting dopamine neurons and driving a further increase in reinforcing effects of the drug.…”
Section: Dendritic Dopamine Transmission and Methamphetamine Self-admsupporting
confidence: 93%
“…This is consistent with previous reports of 2-to-3-fold higher NT levels in the SNc and dorsal striatum following methamphetamine self-administration (Frankel et al, 2011;Hanson et al, 2013). Furthermore, we have shown that blockade or ablation of NT receptors decreases methamphetamine selfadministration (Dominguez-Lopez et al, 2018;Dominguez-Lopez et al, 2019). Taken together, this suggests that methamphetamine use enhances NT-induced LTDDA, disinhibiting dopamine neurons and driving a further increase in reinforcing effects of the drug.…”
Section: Dendritic Dopamine Transmission and Methamphetamine Self-admsupporting
confidence: 93%
“…Neurotensin (Nts) systems have previously been explored in the context of and in circuitries related to AUD, stress disorders, and motivated behaviors [2][3][4][5][6][7] . Levels of neurotensin in the cortex are significantly lower in Alcohol Preferring P-rats as compared to their controls 8 .…”
Section: Neurotensin Systems and Alcoholmentioning
confidence: 99%